Transboundary Movement of Yezo Virus via Ticks on Migratory Birds, Japan, 2020–2021 - Nishino, Ayano; Tatemoto, Kango; Ishijima, Keita; Inoue, Yusuke; Park, Eun-sil; Yamamoto, Tsukasa; Taira, Masakatsu; Kuroda, Yudai; Virhuez-Mendoza, Milagros; Harada, Michiko; Nakamura, Noboru; Morimoto, Gen; et al. (Emerging infectious diseases, 2024)
Migratory birds carry ticks harboring various pathogens, including the zoonotic Yezo virus. In Hokkaido, Japan, we collected ticks from migratory birds during 2020-2021. Eight of 385 pools, comprising 2,534 ticks, tested positive for Yezo virus RNA, suggesting Yezo virus might be spread through the flyways of migratory birds.